MEASUREMENTS OF THE ACUTE TOXICITY OF CYPERMETHRIN TO NILE TILAPIA (Oreochrotnie niloticus), USING A STATIC AND A CONTINUOUS-FLOW SYSTEM - Santosa Koesoemadinata (Research Center for Fisheries, 1996)
Experiments on the toxicity of the insecticide cypermethrin, a synthetic pyrethroid,to nile tilapia (Oreoehromia niloticue) were conducted, using static and continuous flowsystems.